Glycoalkaloids as medicinal agents from callus and regenerated plants of Solanum nigrum var. judaicum - Al-Ashaal, Hanan Abd Al-Hay (Comunicata Scientiae, 2019)
The target of this study is production of glycoalkaloids from cultures of Solanum nigrum var. judaicum Besser. Further, to evaluate their therapeutic effects. S. nigrum var. judaicum leaves were implanted in MS media containing growth regulators for in vitro study. HPLC analyses were applied for qualitative and quantitative determination of glycoalkaloids. Cytotoxic effects against human carcinoma cell lines were evaluated. In addition, antiviral, antioxidant, anti-inflammatory and antiparasitic activities of the formed glycoalkaloids were estimated. HPLC data indicated the success of in vitro solasodine and solanidine glycosides production. Solasonine represented the highest concentration. Biological assays illustrated that obtained glycoalkaloids exhibited cytotoxic activity against human carcinoma cell lines that may be attributed to free radical scavenging activity (69.98%). Strong antiherps performance was observed (94%). In addition, the glycoalkaloids showed in vitro schistomicidal (IC50 76.4 ppm) and fasciolicidal (IC50 76.6 ppm) activities. In vivo anti-inflammatory assay revealed potent activity against carrageenan induced edema. Glycoalkaloids were formed 2-5 folds that of intact plant pointed to the efficiency of the cultures. The present findings referred to the pronounced biological performance of the produced glycoalkaloids including antiviral, cytotoxic anti-inflammatory and antiparasitic activities. Botanical derived medication from S. nigrum var. judaicum could be accomplished guided with the present data.